A Review Paper on Microstrip Patch Antenna (MPA) for 5G Wireless Technology - et. al., Praveen Kumar Patidar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In earlier days larger size antennas were used but due to technological development these larger size antennas were replaced by compact antennas. Microstrip patch antennas have low profile configuration, light weight, easy to fabricate, smaller in dimension and low cast. There is tremendous growth in mobile users in recent years. They need more features on their mobile phone such as high-data-rate speed, reduced traffic, more efficient telecommunication, and real-time applications. The fifth-generation (5G) technology better QoS, high bandwidth, and reduced delay or latency. In this paper, a review is done for microstrip patch antenna along with 5G technology and studied of measurements of various antenna design parameters